Cloning and expression of pullulanase gene from locally isolated bacillus SP - Nik Mahmood, Nik Azmi; Md. Illias, Rosli; Md. Salleh, Madihah; Hassan, Osman; Kamaruddin, Kamarulzaman; Shahab, Neelam (Universiti Teknologi Malaysia, 2006)
Bacterial pullulanase represents one of th e starch-degrading enzymes that are widely used in the starch processing indu stry along with amylases. Amylases hydrolyze a -(1,4 )-glycosidic linkage in starch to produce a mixture of glucose , maltooligo sacchari de and limited a-dextrin. All the remaining a -(1,6)-glycosid ic branches in the products are hydrolyzed by p ullulanase. This is an advantage t o improve glucose production by coupling pullulanase and amylase in the p rocess. As such, many pullulana e enzyme has been isolated and one has been showing optimum pH of 10-10.5 which is suitable for use in dishwasher detergent additive in removal of star ch stain. We have recently iso lated a few bacterias that have shown potentially pullulanase producers by the holo-zone in pullulan-plate assay. One of them, we named Bacillus –1 sho ws a bigger holo-zone among others, Bacillus- 1 is highly active in pH more than 7. The enzyme also shows a mo derate activity to wards starch that may be indicates be side hydrolyzes a -(1,6)-glycosidic linkage in starch, it also hydrolyzes a -(1,4)- glycosidi c simi lar to a -amylase. Unfortunately the enzyme from wild-type bacteria is in lower yield an d in this studies, we intend to clone and sequence the pullulanase gene and also expressed the gene in a high expression system to be able to produce in a high yield before characterizing expressed protein.